2021
DOI: 10.1021/acscatal.1c01111
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Among Dealloying, Ostwald Ripening, and Coalescence in PtXNi100–X Bimetallic Alloys under Fuel-Cell-Related Conditions

Abstract: Platinum-based bimetallic alloys have been largely investigated during the last few years as a valid alternative to bare Pt cathode catalysts for proton-exchange membrane fuel cells (PEMFCs) to improve their cost-efficiency. Nonetheless, Pt bimetallic alloys are characterized by a reduced stability, which is poorly understood at a fundamental level. It is thus essential to describe the entire chain of interconnected degradation mechanisms to formulate a comprehensive model of catalyst degradation that will hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…The total amount of dissolved Ni is in the ballpark of what was reported in precedent studies. 40 The dissolved amount of the other three metals is at least two orders of magnitude smaller. The amount of dissolved Rh is the smallest, which is followed by Pt.…”
Section: Resultsmentioning
confidence: 98%
“…The total amount of dissolved Ni is in the ballpark of what was reported in precedent studies. 40 The dissolved amount of the other three metals is at least two orders of magnitude smaller. The amount of dissolved Rh is the smallest, which is followed by Pt.…”
Section: Resultsmentioning
confidence: 98%
“…In recent years platinum-based bimetallic alloys have been investigated as an alternative to bare platinum cathode catalysts for proton-exchange membrane fuel cells to improve their cost-effectiveness. 128 However, they have a reduced stability, which is poorly understood at a fundamental level. It is necessary to elucidate the entire chain of interconnected degradation mechanisms to formulate a comprehensive model of catalyst degradation that will help interpret bimetallic alloy behaviour.…”
Section: Inorganic Materialsmentioning
confidence: 99%
“…Being applicable for in situ investigations, SAXS has been used to study Ag nanoparticle formation during multipulse electrodeposition . In our previous work, we investigated electrochemical aging by in situ GISAXS and observed changes in the morphology of fuel cell electrodes during simulated operation. A limited number of in situ SAXS studies during templated electrodeposition have been reported in literature. Richardson et al studied the templated electrodeposition of Pt films using phytantriol in inverse bicontinuous lipid cubic phases.…”
Section: Introductionmentioning
confidence: 99%